Application of Google My Business to Increase the Number of Customers - Riki, Riki; Nurlenawatii, Netti; Angela, Flora Patricia (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The aim of this research is to find out the level of use of Google My Business in increasing the number of customers at the RJK Motor Karawang car repair shop. Based on research results, it shows that the level of use of Google My Business in increasing the number of sales customers before the Covid 19 pandemic was said to be very good. Promotion is also an element that needs to be considered. The success of a promotional activity carried out by a company is greatly influenced by promotional mix variables. Selection of appropriate, efficient and effective promotional mix variables is the main key to a company's promotional activities. The promotional mix carried out at the RJK Motor Karawang car repair shop is personal selling. Meanwhile, personal selling involves seeking orders from government and private agencies. So there is a positive relationship between promotional activities carried out and the value of sales of services obtained. The higher the value used, the higher the sales value obtained. Because there is a strong relationship between promotional costs and sales value, the RJK Motor Karawang car repair shop should create attractive promotional activities and increase its promotional activities. The research results show that the use of Google My Business in increasing the number of consumers has a high willingness to create increased promotions also makes the company better.